Needs of health education for community residents – A survey across difference types of community in Hangzhou of China - Minzhe Yi; Qingtao Gao; Xianxiao Yang; Weiwei Chen (Chinese General Practice Journal)
Background: Community-based health education is widely recognized as a cost-effective means to improve public health. However, current research on health education needs lacks a framework that accounts for variations across different community types, limiting understanding of diverse health education needs in urban settings. Objective: This study examines health education needs across various community types, aiming to identify significant differences that can inform community health education strategies. Methods: Conducted in Hangzhou from April to June 2024, this mixed-method study used purposive sampling to select residents from heterogeneous, transformed, homogeneous, and system-based communities for interviews exploring health education needs and existing practices. Qualitative data from 14 interviews and 21 policy documents were coded at three stages and analyzed using Nvivo 12.0, resulting in themes that informed a survey design. In the quantitative phase, 299 residents completed a questionnaire assessing health education needs on a 5-point Likert scale. Descriptive statistics, non-parametric tests, and multivariate logistic regression models were employed to assess health education needs and analyze differences across community types. Results: Eight primary health education topics were identified: major disease prevention, healthy lifestyles, maternal and child health, mental health, environmental health, medication safety, emergency response, and sexual health education, with 23 sub-topics. First aid knowledge education showed the highest demand [5 (4,5)], followed by cancer prevention education [4 (4,5)]. Non-parametric tests indicated significant influences on health education needs by education attainment, income, and community type (P < 0.05). Multivariate logistic regression model analysis revealed significant variation in needs based on education for diabetes prevention and life safety education, income for cardiovascular and infectious disease prevention, and community type for natural environmental pollution prevention, infectious disease prevention, diabetes and cardiovascular education, and first aid knowledge, life safety education (P < 0.05). Conclusion: Differences in health education needs are shaped by factors such as residents' education attainment, income, and access to community health resources. Targeted health education should be developed to address specific needs of each community type while promoting equitable resource distribution.